(KAJIAN REVIEW: MODEL INOVATIF CONTEXTUAL TEACHING AND LEARNING BERBANTUAN TEKNOLOGI DALAM PEMBELAJARAN MENULIS PUISI - Ari Kartini; Dadang Sunendar; Sumiyadi; Yulianeta (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2025)
This research is a review study with the aim of describing the role of the Contextual Teaching and Learning model in learning and describing the design of the CTLS model assisted by the MCP application. Research sources are taken from articles that have been published in accredited and reputable journals. The research techniques used are, (1) data reduction; (2) data presentation; and (3) drawing conclusions/verification. Based on the study of the analysis process results, the findings of this research are; 1) The CTL model is still widely used in learning both in the fields of science and social humanities; 2) The application of the CTL model is effectively used in learning both in the science and social fields; 3) The application of the CTL model has been developed through the integration of other components, including contextual learning FRAME (Formulate, Observe, State, Combine, Communicate and Practice); contextualized learning with linked open data; Contextual Cb-model; (E-LKPD) Contextual Teaching and Learning; E-Module Based on Contextual Teaching and Learning; Blended Learning with Flipped Classroom Through a Contextual Teaching and Learning Approach; Learning Tool For Robotics Basic Programming Based on Contextual Teaching And Learning Contextual Teaching Learning (Ctl) Based on Information and Communication of Technology (ICT); Adaptive Contextual Learning Model of Integrated Science by Integrating Digital Age Literacy; ICT-Based Contextual Mathematics Learning. 4) Based on the results of the review study, the innovation findings from this research are the design of developing an innovative CTL model which is paired with the Stratta strategy with the help of technology in the form of the Mobile Cipta Poetry application. The CTLS model assisted by the MCP application in poetry writing activities was developed with the following syntax; exposition, interpretation, creation, inclusion, and review. Based on research findings, it can be concluded that the CTL model is still suitable for use in learning. In this regard, as a basis for further research, the CTLS model assisted by the MCP application developed can be followed up and its effectiveness tested.